Small-scale analysis of exopolysaccharides from Streptococcus thermophilus grown in a semi-defined medium - Levander, Fredrik (BioMed Central, 2001)
BACKGROUND: Exopolysaccharides (EPSs) produced by lactic acid bacteria are important for the texture of fermented foods and have received a great deal of interest recently. However, the low production levels of EPSs in combination with the complex media used for growth of the bacteria have caused problems in the accurate analysis of the EPS. The purpose of this study was to find a growth medium for physiological studies of the lactic acid bacterium Streptococcus thermophilus, and to develop a simple method for qualitative and quantitative analysis of EPSs produced in this medium. RESULTS: A semi-defined polysaccharide medium was developed and evaluated on six strains of Streptococcus thermophilus. The EPSs were analysed using a novel protocol incorporating ultracentrifugation for the removal of interfering sugars, hydrolysis and analysis of the monomer composition by High Performance Anion-Exchange Chromatography with pulsed amperometric detection. The medium and analysis method allowed accurate quantification and monomer analysis of 0.5 ml samples of EPSs from tube cultures. CONCLUSIONS: The presented medium should be useful for physiological studies of S. thermophilus, and, in combination with the method of analysis of EPS, will allow downscaling of physiological studies and screening for EPSs.